2017
DOI: 10.1515/joim-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Challenges and Organizational Cynicism: A study on Egyptian Physicians

Mohamed Mousa

Abstract: As a result of globalization and interactions of people with various identities, cultural diversity has become a noticeable norm in today's business life. Accordingly, managing such cultural diversity requires a dependence on a much more tolerant culture in which employees seek to attain both career and organizational objectives without being hurdled by irrelevant factors of religion, race, ethnicity and so on. During the last two decades, organizational cynicism has found a place in academic management litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similarly, Abugre (2017) found that employees' satisfaction can be increased through effective interpersonal interactions and engagement that will help in reducing OC at workplace. It was also evident from previous studies that EE matters within an organisation, on the one hand, and that disengaged employees, on the other hand, increased costs for an organisation due to high absenteeism (Mousa, 2017a), lower productivity and high turnover of staff (Saari and Judge, 2004;Truss et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, Abugre (2017) found that employees' satisfaction can be increased through effective interpersonal interactions and engagement that will help in reducing OC at workplace. It was also evident from previous studies that EE matters within an organisation, on the one hand, and that disengaged employees, on the other hand, increased costs for an organisation due to high absenteeism (Mousa, 2017a), lower productivity and high turnover of staff (Saari and Judge, 2004;Truss et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, there are authors who argue that Diogenes was the founder of cynicism and had no links with Antisthenes whatsoever (Sayer, 1945). OC is closely related to other constructs that include work alienation, job satisfaction, trust, EP, burnout and psychological contract violation (Dean et al , 1998; Johnson and O’Leary-Kelly, 2003; Storm and Rothmann, 2003; Yildiz and Şaylikay, 2014; Simha et al , 2014; Nicholson et al , 2014; Delken, 2004; Mousa, 2017a, b). Job satisfaction, as an attitudinal variable, is confined to a particular setting where the employee performs tasks and is revealed only in the responses that arise immediately from these task settings.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations